De “microcosmos” a actor principal del cambio en el rock argentino: Veinte años de usos del indie en Buenos Aires desde una perspectiva etnográfica e histórica - Boix, Ornela (Notas de Antropología de las Américas, 2023)
In this work we show how indie became a central reference of Argentine popular music in the first two decades of the 21st century. From a methodological strategy that combines ethnographic and documentary data, we argue that the term indie, which cannot be reduced to a set of stylistic features, is successful because of its use in local scenes, where it summarizes a way of doing around music, that is deeply embedded in the everyday life of groups of musicians, artists, and other participants.